Pengaruh Trust dan Kohesivitas Kelompok Terhadap PengambilanKeputusan di Moderasi Oleh Kecerdasan Emosional Pada UKM KMPA “Ranti Pager Aji” Universitas Islam Malang - Alivia Nur Yuana; Pardiman Pardiman; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to analyze the influence of trust, and cohesiveness on decision making moderated by emotional intelligence contained in KMPA UKM "Ranti Pager Aji" Universitas Islam Malang. Sampling in this study used saturated sampling, namely by using the entire existing population to be used as a sample. The data analysis method used in this study is by using outer model and inner model testing. Based on the results of the study, it is known that trust and group cohesiveness have a significant effect on decision making. However, on the moderation effect of emotional intelligence does not exert a significant influence  of trust, and group cohesiveness on decision making. (Times New Roman; Keywords: Trust, Group Cohesiveness, Decision Making, Emotional Intelligence